On the critical competition between singlet exciton decay and free charge generation in non-fullerene based organic solar cells with low energetic offsets - Pranav, Manasi; Shukla, Atul; Moser, David; Rumeney, Julia; Liu, Wenlan; Wang, Rong; Sun, Bowen; Smeets, Sander; Tokmoldin, Nurlan; Cao, Yonglin; He, Guorui; Beitz, Thorben; et al. (Energy and Environmental Science, 2024)
Reducing voltage losses while maintaining high photocurrents is the holy grail of current research on non-fullerene acceptor (NFA) based organic solar cell. Recent focus lies in understanding the various fundamental mechanisms in organic blends with minimal energy offsets - particularly the relationship between ionization energy offset (ΔIE) and free charge generation. Here, we quantitatively probe this relationship in multiple NFA-based blends by mixing Y-series NFAs with PM6 of different molecular weights, covering a broad power conversion efficiency (PCE) range: from 15% down to 1%. Spectroelectrochemistry reveals that a ΔIE of more than 0.3 eV is necessary for efficient photocurrent generation. Bias-dependent time-delayed collection experiments reveal a very pronounced field-dependence of free charge generation for small ΔIE blends, which is mirrored by a strong and simultaneous field-dependence of the quantified photoluminescence from the NFA local singlet exciton (LE). We find that the decay of singlet excitons is the primary competition to free charge generation in low-offset NFA-based organic solar cells, with neither noticeable losses from charge-transfer (CT) decay nor evidence for LE-CT hybridization. In agreement with this conclusion, transient absorption spectroscopy consistently reveals that a smaller ΔIE slows the NFA exciton dissociation into free charges, albeit restorable by an electric field. Our experimental data align with Marcus theory calculations, supported by density functional theory simulations, for zero-field free charge generation and exciton decay efficiencies. We conclude that efficient photocurrent generation generally requires that the CT state is located below the LE, but that this restriction is lifted in systems with a small reorganization energy for charge transfer.
CRIS-Team Scopus Importer:2024-10-04